Autonomy and Islamic Criminal Law Enforcement in Creating Social Order in Aceh Region - Anwar, Syahrul; Ramli, Mohd Anuar; Nuruddien, Muhammad (Shariah Faculty UIN Maulana Malik Ibrahim Malang, 2025)
This study departed from the special status of Aceh as the only province in Indonesia granted specific authority to implement Islamic law through Law No. 11 of 2006 concerning the Government of Aceh. One of the manifestations of this special status is the existence of the Sharia Court, which holds the authority to adjudicate jinayah (Islamic criminal) cases, such as khalwat (close proximity between unmarried individuals), maisir (gambling), and khamar (alcohol consumption). This research aims to analyse how the Sharia Court performs its judicial function in resolving jinayah cases, the challenges it faces in practice, and the effectiveness of jinayahenforcement in fostering justice and social order. The method used is an empirical juridical approach, with data collected through interviews, document analysis, and direct observation. The findings reveal that the Sharia Court plays a significant role in enforcing Islamic criminal law in Aceh. However, the implementation of the jinayahstill faces several obstacles, particularly regarding coordination among law enforcement agencies, limited human resources, and resistance from certain segments of society toward the jinayah law. These findings suggest that the success of jinayahenforcement is not solely dependent on regulations but also on the readiness of judicial institutions, community support, and synergy among legal enforcement bodies. This study is expected to make a significant contribution to the evaluation and reinforcement of the Sharia judicial system within the framework of Aceh’s special autonomy, while offering strategic recommendations to enhance the effectiveness of Islamic law enforcement that is just and sustainable.